2000
DOI: 10.1007/s004380050042
|View full text |Cite
|
Sign up to set email alerts
|

Minicircular plastid DNA in the dinoflagellate Amphidinium operculatum

Abstract: Plastid DNA was purified from the dinoflagellate Amphidinium operculatum. The genes atpB, petD, psaA, psbA and psbB have been shown to reside on single-gene minicircles of a uniform size of 2.3-2.4 kb. The psaA and psbB genes lack conventional initiation codons in the expected positions, and may use GTA for translation initiation. There are marked biases in codon preference. The predicted PsbA protein lacks the C-terminal extension which is present in all other photosynthetic organisms except Euglena gracilis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 17 publications
5
98
0
Order By: Relevance
“…If the model of recombination among cores is correct (Zhang et al, 1999(Zhang et al, , 2002Barbrook & Howe, 2000) then the hypervariable sequences of the Symbiodinium V regions would indicate that these do not homogenize or recombine nearly as often as the cores. It is possible that the V regions act as buffer zones lowering the probability that recombination will extend into the protein-coding regions of minicircles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the model of recombination among cores is correct (Zhang et al, 1999(Zhang et al, , 2002Barbrook & Howe, 2000) then the hypervariable sequences of the Symbiodinium V regions would indicate that these do not homogenize or recombine nearly as often as the cores. It is possible that the V regions act as buffer zones lowering the probability that recombination will extend into the protein-coding regions of minicircles.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, core regions are identifiable across all the minicircles from Amphidinium operculatum, again implying intra-circle recombination (Barbrook & Howe, 2000;Howe et al, 2003), but the sequence of these cores is not alignable with those from Heterocapsa triquetra. A hypothesis of species-specific conserved cores has been tested on two minicircles, psbA and 23S rDNA, from three further species of Heterocapsa and from the distantly related A. carterae, and was supported in each case (Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some time after the haptophyte replacement of the plastid, the dinoflagellates diverged into two groups. One group retained the ancestral haptophyte characteristics in its plastid (fucoxanthin, chlorophyll c 1 ϩ c 2 ), whereas the second group underwent several major changes including the evolution of peridinin (replacing fucoxanthin), loss of chlorophyll c 1 , the remarkable reduction of its plastid genome to single gene circles (7,39), the development of cellulose armor, and the origin of a divergent nuclear encoded ''Form II'' rbcL gene (40,41). It is possible that peridinin could have evolved from a modification of the ancestral fucoxanthin biosynthesis pathway because these are structurally related xanthophylls (for details, see refs.…”
Section: Evolution Of Dinoflagellate Plastidsmentioning
confidence: 99%
“…Uchida (1988) showed that peridinin dinoflagellates have a divergent ferredoxin and later found that dinoflagellate psbA sequences are also extremely divergent from other algae (Takishita and Uchida 1999). Using density gradient centrifugation Zhang (1999) and later Barbrook and Howe (2000) as well as Hiller (2001), and Bachvaroff (unpublished) have separated circular, or plasmid-like DNAs from peridinin dinoflagellates. These minicircles encode one or sometimes two genes, although partial or incomplete genes have also been found (Hiller 2001).…”
Section: Bmentioning
confidence: 99%